2017
DOI: 10.1007/s10995-017-2386-9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Home and School Environments on Children’s Diet and Physical Activity, and Body Mass Index: A Structural Equation Modelling Approach

Abstract: Introduction The home and school environments play important roles in influencing children's health behaviours. However, their simultaneous influence on childhood obesity has not yet been examined. We explore the relationship of the home and school environments with childhood obesity, to determine whether this relationship is mediated by children's fruit and vegetable intake and physical behaviours. Methods This study uses baseline data from 9 to 11 year old children, their parents and school principals (match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
2
23
0
3
Order By: Relevance
“…Our finding of no association between quality of school physical activity environments and student weight status is consistent with Haddad et al’s (2018) study of approximately 2500 school children in the same age group set in both rural (32%) and metropolitan (68%) areas of South Australia [ 35 ]. Haddad and colleagues found the quality of the home environment was more strongly associated with students’ measured BMI than the school environment.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of no association between quality of school physical activity environments and student weight status is consistent with Haddad et al’s (2018) study of approximately 2500 school children in the same age group set in both rural (32%) and metropolitan (68%) areas of South Australia [ 35 ]. Haddad and colleagues found the quality of the home environment was more strongly associated with students’ measured BMI than the school environment.…”
Section: Discussionsupporting
confidence: 92%
“…For example, using food as an emotional regulator or reward, and allowing a child full autonomy over their feeding environment have been associated with overconsumption of calories, and possibly higher child BMI in western populations (24, 25). Additionally, parental modeling of healthy food intake, creation of a healthy diet and home environment may also be helpful for promoting optimal BMI in children (26). There are currently no longitudinal studies examining if these feeding practices are associated with subsequent child weight, or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…The school has been identified as a location that promotes PA [55,56,57]. Previous research has identified key windows during the day to contribute to school-based PA, as break time and other extracurricular periods provide opportunities for PA and fitness [58].…”
Section: Discussionmentioning
confidence: 99%